Analisis Karakter Berdasarkan Penilaian Diri Peserta Didik dan Persepsi Guru di SMPN 35 Medan - Simamora, Joice Evelyn; Daulay , Tania Azzahra; Hapsyah , Syahrira; Tarigan , Reva Nesiya; Nurbalqis , Natasya (Universitas Negeri Medan, 2024)
Character can be defined as an individual's personality, which is shaped by a combination of positive beliefs and values, providing a foundation for perspective, thought, attitude, behavior, and action. This research employs quantitative descriptive data analysis techniques to examine the character of students at SMPN 35 Medan. The data sources for this study were students’ self-assessments and teachers' perceptions. The dimensions under investigation include honesty, responsibility, empathy, social aspects, and self-confidence. The data were collected through questionnaires, interviews, and observations involving a sample of 25 students. The results demonstrated that the dimensions of discipline and social aspects exhibited the highest levels of development, with a value of 64%. This was followed by the dimensions of responsibility and empathy, which demonstrated a percentage of 60%. Finally, the dimension of self-confidence exhibited the lowest level of development, with a percentage of 28%. This study recommends the crucial role of teachers in shaping students' character through literacy programs, interactive methods, and educational sanctions.